2005
DOI: 10.1063/1.1947392
|View full text |Cite
|
Sign up to set email alerts
|

Nontrivial dependence of dielectric stiffness on bias field in relaxors and dipole glasses

Abstract: Dielectric permittivity and Second Harmonic Generation (SHG) studies in the field-cooled mode show a linear dependence of dielectric stiffness (inverse dielectric permittivity) on dc bias in PMN-PT crystals and SHG intensity in KTaO3:Li at small Li concentrations. We explain this unusual result in the framework of a theory of transverse, hydrodynamic-type, instability of local polarization.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Usually, the surface effect in ferroelectric ceramics is related to the deadlayer [1,10], but, it follows from our observation that, in reality, the dead layer is a result of the action of the random fields with the source in the inter-crystallite interface. Thus, indirectly, our data are supported by the theories of tunability of small-crystallite-size ceramics employing the idea of the dead layer [10,11].…”
Section: Ceramics Compositionsupporting
confidence: 78%
“…Usually, the surface effect in ferroelectric ceramics is related to the deadlayer [1,10], but, it follows from our observation that, in reality, the dead layer is a result of the action of the random fields with the source in the inter-crystallite interface. Thus, indirectly, our data are supported by the theories of tunability of small-crystallite-size ceramics employing the idea of the dead layer [10,11].…”
Section: Ceramics Compositionsupporting
confidence: 78%
“…Details of dielectric studies have been described elsewhere. 5,7 The majority of our experimental data have been obtained in the 1 -100 kHz frequency range. It is well documented in the literature that, in the case of the PMN-PT compositions, this range is wide enough to demonstrate the frequency dispersion of permittivity and the frequency shift of T m .…”
Section: Resultsmentioning
confidence: 99%
“…In relaxors, such a dependence has also been observed above some threshold field, and it was explained by the divergence of the transverse susceptibility. 7 Poplavko 39 assumed that the average relaxation time in relaxors decreases with the increase of bias field. Tagantsev and Glazounov 38 suggested that the vibration of PNR's can be described by the following field dependence of the relaxation time: = 0 exp͓͑U − VPE͒ / k B T͔ where V is the PNR's volume and P the polarization magnitude inside PNR's.…”
Section: ͑6͒mentioning
confidence: 99%
See 2 more Smart Citations